ANALYSIS OF STAKEHOLDER CONTRIBUTIONS TO THE DEVELOPMENT OF MSMEs COMPETITIVENESS - Arqani, Alfen; Hulwati, Hulwati; Meirison, Meirison; Ahmad, Shofian (Ekonomi Islam, 2025)
Research aims: This study analyzes the contributions of key stakeholders government agencies, the Ministry of Religious Affairs, community leaders, and MSME owners in strengthening the competitiveness of halal MSMEs in Kerinci Regency. Design/Methodology/Approach: The research uses a field-based qualitative descriptive method. Data were collected through observation, interviews, and documentation with purposively selected informants: the Cooperative and Manpower Office, the Ministry of Religious Affairs, community leaders, and MSME owners. Data were analyzed through reduction, presentation, and conclusion drawing, supported by triangulation for credibility. Research findings: The results show that stakeholder involvement is important but not yet optimal. Government initiatives such as training, DUMISAKE capital assistance, and free halal certification through the SEHATI program support MSME competitiveness. However, challenges persist, including uneven assistance, limited socialization, restricted technology access, and weak coordination among stakeholders. The role of community leaders remains minimal. Theoretical Contribution/Originality: This study enriches Islamic economic literature by showing how stakeholder synergy influences halal MSME competitiveness in a regional context. Practitioners/Policy Implications: Enhanced coordination, stronger outreach, improved digital access, and continuous monitoring are needed to increase program impact. Research Limitations/Implications: Findings are limited to Kerinci Regency and qualitative perspectives; broader comparative studies are suggested.